Conquering the Low‐k Death Curve: Insulating Boron Carbide Dielectrics with Superior Mechanical Properties. (30th May 2016) - Nordell, Bradley J.; Nguyen, Thuong D.; Keck, Christopher L.; Dhungana, Shailesh; Caruso, Anthony N.; Lanford, William A.; Gaskins, John T.; Hopkins, Patrick E.; Merrill, Devin R.; Johnson, David C.; Ross, Liza L.; Henry, Patrick; et al.
Abstract : To enable the continued scaling of integrated circuits, the semiconductor industry faces ongoing struggles to implement better low‐dielectric‐constant (low‐ k ) materials within the interconnect system. One of the biggest challenges to integrating new dielectrics is overcoming the low‐ k death curve—that is, the fatal falloff in mechanical properties associated with the low material densities required to achieve low k values. It is shown that amorphous hydrogenated boron carbide (a‐BC:H) films exhibit Young's modulus ( E ) values between two and ten times greater than those of state‐of‐the‐art Si‐based dielectric materials across a wide range of k values. In particular, optimized a‐BC:H films with moderate k values in the range of 3–4, in addition to possessing outstanding stiffness ( E ≈ 100–150 GPa), simultaneously exhibit excellent electrical properties (leakage current of <10 –8 A cm –2 at 2 MV cm –1 and breakdown voltage of >5 MV cm –1 ). Films in this range also demonstrate resistance to Cu diffusion to at least 600 °C, as well as chemical stability and etch properties suitable for low‐ k diffusion barrier/etch stop applications. Abstract : Amorphous hydrogenated boron carbide films exhibit Young's modulus ( E ) values greater than those of state‐of‐the‐art Si‐based low‐ k dielectric materials. Moderate‐density a‐BC:H films with dielectric constant ( k ) values of 3–4 possess outstanding stiffness ( E = 100–150 GPa), excellent leakage current (<10 –8 A cm −2 at 2 MV cm −1 ), resistance to Cu diffusion, and etch properties suitable for low‐ k diffusion barrier/etch stop applications.